G Protein Coupled Receptor 87 (GPR87) in end stage kidney and associated tumors - Beöthe, Tamás; Kovacs, Gyula; Peterfi, Lehel (Anticancer research, 2024)
Background/Aim: End-stage renal disease (ESRD) and acquired cystic renal disease (ACRD) are characterized by progressive inflammation, structural remodeling and by development of unique cancer types. Eosinophilic-vacuolated and chromophobe-like renal cell carcinoma develop exclusively in ACRD kidney. The aim of the study was to investigate the molecular mechanism of ESRD/ACRD carcinogenesis. Materials and Methods: Our previous Affymetrix array analysis detected GPR87 as one of the highly and specifically expressed genes in ESRD/ACRD kidneys. In this study we analyzed normal and ESRD/ACRD kidneys and related tumors for GPR87 expression by PCR, RT-PCR, and immunohistochemistry. Results: Immunohistochemistry revealed a strong GPR87 expression in proliferating epithelial cells in ESRD/ACRD kidneys and in cells of eosinophilic-vacuolated and chromophobe-like renal cell carcinoma. Conclusion: GPR87 signaling plays an important role in the structural remodeling of ESRD/ACRD kidney and development of ACRD-associated tumors with unique histology.